the Traditional Wisdom of Plant and Animal Conservation on the West Java and the NAD Aceh Darussalam, Indonesia - Munandar, Achmad; Apriana, Evi (Proceeding International Conference on Global Resource Conservation, 2013)
The degradation of plant and animal of Indonesia was high, approximately 30-40 percent (2011). The growth of Indonesian population and industry was highest, especially on Java island and the significance effect to degrade of plant and animal. The Indonesian environments have many types of niche or habitat of plant and animal as ecosystem and the Indonesian peoples have many ethnics and the local culture, especially the local culture to environment. The attitude of the people to the environment or ecosystem to be able positive or negative action. The positive action as a value for the ecosystem and human being. The description of research using the qualitative research. the place of research on Kampung Naga, Tasikmalaya, West Java, Province and Banda Aceh, Province Aceh Darussalam, 2011/2012. The outcome of research was implemented to the university on the subject matter of Biology Conservation and got positive response by student. The outcome of the research on Kampung Naga were invented i.e. the conservation plant and animal on Ciwulan river; the conservation of plant, especially endemic plants and the animals of the environment; the traditional of family planning; the reserve rice and the other food. The outcome of the research of Aceh province i.e. the conservation method of forest; the method of honey take; the traditional method of rice field. The conclusion of the research i.e. the traditional wisdom on Nusantara as the alternative of method of conservation and to the equilibrium of nature. Â Keywords: conservation method of forest, local culture, qualitative research, traditional family planning, traditional wisdomÂ Â